2019
DOI: 10.4236/wjns.2019.92003
|View full text |Cite
|
Sign up to set email alerts
|

Extracranial Carotid Atherosclerosis and Acute Ischemic Stroke in a Tertiary Hospital in Burkina Faso

Abstract: Objective: To determine the prevalence and risk factors of carotid atherosclerosis among ischemic stroke patients in a tertiary hospital in Burkina Faso. Methodology: This was a descriptive and analytical retrospective study of patients admitted at neurology department of Yalgado Ouedraogo University Teaching Hospital with ischemic stroke and cerebral large vessel atherosclerosis in the period from January 1, 2012 to December 31, 2016. Results: The prevalence of extracranial carotid atherosclerosis was 23.9%. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 30 publications
3
3
1
Order By: Relevance
“…Among the cases with atherosclerosis in the current study, DM was detected in 17.8%. The frequency of DM in our study is similar to Dabilgou et al (20) who showed that diabetic patients represent 15.3% of the cases in their study. DM is an important risk factor for extracranial carotid atherosclerosis (16, 18, and 19) .…”
Section: Discussionsupporting
confidence: 91%
“…Among the cases with atherosclerosis in the current study, DM was detected in 17.8%. The frequency of DM in our study is similar to Dabilgou et al (20) who showed that diabetic patients represent 15.3% of the cases in their study. DM is an important risk factor for extracranial carotid atherosclerosis (16, 18, and 19) .…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the prevalence of increased CIMT was higher in participants above 60 years and age was positively associated with increased CIMT. This agrees with most global studies that show increased CIMT, carotid plaque, and carotid stenosis being more common in older people than in younger people [19][20][21]. Elevated LDL cholesterol was also associated with an increased CIMT.…”
Section: Carotid Intima Thicknesssupporting
confidence: 91%
“…Studies on the prevalence of carotid stenosis in stroke patients in Africa have yielded varying ranges of prevalence with older studies documenting absence or a very low prevalence of carotid stenosis [5,29] while the more recent studies indicate a prevalence between six to thirty percent [20]. The prevalence in this study is higher than documented by Nakibuuka et al, [26], who found no evidence of carotid stenosis as a cause of stroke a decade ago.…”
Section: Carotidcontrasting
confidence: 54%
See 2 more Smart Citations